Comment on “cancer may be induced by microplastics-sorbed polycyclic aromatic hydrocarbons?” - Parthasarathy Surya; A. Sundaramanickam; Nithin Ajith (Oral Oncology Reports)
Microplastics, pervasive environmental contaminants, pose a potential risk to human health, including the development of oral carcinoma. These minute plastic particles infiltrate various environmental niches and enter the human body through ingestion, inhalation, and dermal exposure. Detected in organs such as the gastrointestinal tract and respiratory system, microplastics may induce inflammation and organ dysfunction. Emerging research suggests their potential to harbor carcinogenic substances, leading to DNA damage and carcinogenesis. Genotoxicity studies inform risk assessment and regulatory decisions. Future research should elucidate the mechanistic pathways linking microplastics to oral carcinoma, focusing on tissue accumulation, inflammation, and DNA damage in the oral cavity. Mitigation strategies should encompass regulatory measures, public awareness campaigns, and advancements in dental care products to address the burgeoning health risks posed by microplastic pollution.